Solved Question Papers of Pathology and Genetics for BSc Nursing - Akhtar Shamim; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2012)
This book Pathology and Genetics for BSc Nursing is a unique approach by simplifying the topics, enabling students for sure success in examination while ensuring highest attainable standards of medical education and related practices in the field of Nursing and Allied Sciences. A clear, concise and complete format of answers to important and frequently asked questions along with the explanation of all options of the multiple choice questions (MCQs) related to each topic. Student-friendly guide enriched with techniques and simple tips ensuring speed in solving the MCQs. Greater and in-depth understanding through concise answers to short answers questions (SAQs) and complete answers to long answers questions (LAQs). This book focuses on completion of the syllabus in the least possible available time during examinations, thereby ensuring confidence building and best possible performance of the BSc Nursing students.
Keywords: Genetics,MCQs and Self-assessment,Pathology; Electronic books